DOI: 10.14264/uql.2015.378
|View full text |Cite
|
Sign up to set email alerts
|

Population estimation methods, home range and habitat use for wild red deer (Cervus elaphus) at Cressbrook Dam, south-eastern Queensland

Abstract: Estimating Abundance: Walked line transect distance sampling, aerial line transect distance sampling, vehicle based spotlight counts and faecal pellet counts were used to estimate or obtain indices of abundance of wild red deer at Cressbrook Dam. For each method the labour input, costs and precision were estimated. Spotlighting performed best overall when comparing labour and costs with precision, but had a number of limitations. Walked line transects gave estimates of adequate and repeatable precision but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…A pilot study is particularly useful in determining if the sampling method is suitable for the study site, and may indicate the sampling eff ort required to achieve the survey goals. We used a pilot study eff ectively for the distance sampling method (Amos 2010) to determine the transect line length as described in Buckland et al (2001) to achieve reasonable precision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pilot study is particularly useful in determining if the sampling method is suitable for the study site, and may indicate the sampling eff ort required to achieve the survey goals. We used a pilot study eff ectively for the distance sampling method (Amos 2010) to determine the transect line length as described in Buckland et al (2001) to achieve reasonable precision.…”
Section: Discussionmentioning
confidence: 99%
“…Observers noted the species and group number of the target animals whilst traversing the transects at a speed of approximately 2.4 km h ‐1 . A pilot study (Amos 2010) suggested sampling should be conducted in spring (September to November) when deer groups were the largest and easiest to detect. Transects were undertaken within 2 hours of sunset to avoid possible complications with morning fog but when deer were active after resting in the middle of the day.…”
Section: Methodsmentioning
confidence: 99%
“…Length−weight relationships were developed from adult male and female sambar deer shot and weighed in Victoria in 2012 (Table S1; Bartareau 2019;Watter et al 2020;Hampton et al 2021). We did not have access to equivalent data for red deer, so body mass estimates were based on published estimates for adult male and female red deer (Amos 2015). Final estimated mass and drug doses were adapted upon visual inspection of each deer by the veterinarian (Tables 1 and S1).…”
Section: Equipment and Proceduresmentioning
confidence: 99%